Effectiveness of braille and audio-tactile performance technique for improving oral hygiene status of visually impaired adolescents - Sushmita Deshpande; Ladusingh Rajpurohit; Vivian Varghese Kokka (Wolters Kluwer Medknow Publications, 2017)
Background: Visually impaired people encounter numerous challenges in their daily life which makes it a cumbersome task to pay special attention to oral health needs. Furthermore, there is little knowledge about oral health practices among caretakers and visually impaired individuals, due to which oral health is often neglected when compared to the general health. Hence, there was a need to educate visually challenged individuals about oral hygiene practices in a customized format so that the comprehension of brushing techniques could be conveyed at its best. Materials and Methods: The present study was a randomized control trial of sixty visually impaired adolescents who were divided into three groups of 20 each. In Group 1, Braille was used, whereas in Group 2, audio-tactile performance (ATP) technique and in Group 3, a combination of both the methods were used to teach tooth brushing as a part of oral health education. Pre- and post-plaque index score using Silness and Loe (1967) after health education were calculated and tabulated for statistical analysis. Results: The postintervention mean plaque index score increased in Group 1 from 29.45 to 42.98, whereas the mean plaque score decreased in Groups 2 and 3 from 30.83-29.9 to 30.23-18.73, respectively. Intergroup comparison of postplaque index score using Kruskal-Wallis and ANOVA analysis showed significant difference among all three study groups. Conclusion: The combination of Braille and ATP technique of health education served as the most effective medium to teach oral hygiene methods to visually impaired adolescents.